2018
DOI: 10.1021/acs.jpcc.8b06770
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline-Size Dependence of Dual Emission Peak on Hybrid Organic Lead-Iodide Perovskite Films at Low Temperatures

Abstract: In this work, we have investigated the crystalline-size dependence of optical absorption and photoluminescence emission of CH 3 NH 3 PbI 3 films, which is necessary to identify the potential practical applications of the gadgets based on perovskite films. This study was carried out at low temperatures to minimize the extra complexity induced by thermal effects. The purpose was to clarify the origin of the dual emission peak previously reported in the literature. We found that the grain size is responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 62 publications
(146 reference statements)
2
10
0
Order By: Relevance
“…It can be recognized as a peculiarity lying in a sharp reversal of the continuous/monotonous variation of the lifetime. These characteristic minima agree with the observed shifts, drops, broadenings, and disappearances of the temperature-dependent data of the PL peak energy of the two bands 4 and could be originated from the phase transition. 44 The different lifetimes obtained for the different morphologies by using the GBSe 30 can be linked to different recombination channels (see Figures 3 and 4 a): The emission with the longest lifetime, τ LG , on the order of several to 10 ns is dominant in the configuration of large grains (352 nm-CL, see Figure 3 and solid green triangles in Figure 4 a).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It can be recognized as a peculiarity lying in a sharp reversal of the continuous/monotonous variation of the lifetime. These characteristic minima agree with the observed shifts, drops, broadenings, and disappearances of the temperature-dependent data of the PL peak energy of the two bands 4 and could be originated from the phase transition. 44 The different lifetimes obtained for the different morphologies by using the GBSe 30 can be linked to different recombination channels (see Figures 3 and 4 a): The emission with the longest lifetime, τ LG , on the order of several to 10 ns is dominant in the configuration of large grains (352 nm-CL, see Figure 3 and solid green triangles in Figure 4 a).…”
Section: Resultssupporting
confidence: 89%
“…Only for 103 nm-IS, there is no coexisting crystallographic phases. The details of the PL spectra can be found in refs ( 1 ) and ( 4 ). Figure 2 a–f shows the representative groups of normalized PL transients registered under relatively high excitation fluencies (370 nJ/cm 2 ) for the three types of morphologies studied: 550 nm-CS, 352 nm-CL, and 103 nm-IS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of our own experimental data in Fig. 4(a), the best fitting parameters are E g = 1.643 eV, (R * y ) ≈ 12.5 meV (with an excitonic linewidth of around 30 meV), which is consistent with a similar fitting procedure to experimental results in the temperature range of 150-300 K (tetragonal phase of MAPI) [45].…”
Section: B Analysis Of Spontaneous Emission and Ase Spectrasupporting
confidence: 86%
“…[ 54,55 ] In addition, the grain size of conventional CH 3 NH 3 PbBr 3 bulk crystals can also determine which band structure dominates the overall PL spectra in between different structural phases (e.g., tetragonal‐to‐orthorhombic phase transition) at low temperature (e.g., 40–50 K), generating a dual‐color emission when the same weight in both bands is achieved upon an optimum grain size of about 100 nm. [ 56 ] Recently, Wu et al clarified that dual‐color emission is even a common character of all lead halide perovskites, but the relative intensity of the low‐energy peak (i.e., at longer wavelength) strongly depends on the surrounding conditions, such as the environmental temperature, and can lead to a nondistinguishable second peak in some cases. [ 57 ] The authors confirmed the existence of indirect tail states below the direct transition edge due to the dynamic Rashba splitting effect in APbBr 3 (A = CH 3 NH 3 + , CH(NH 2 ) 2 + , Cs + ) single crystals, which was originated from the thermal polar distortions of the PbBr 6 octahedra at increased temperatures.…”
Section: Direct–indirect Transitions Induced Dual‐color Emissionmentioning
confidence: 99%